The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.micres.2017.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, purification, structural elucidation and antimicrobial activities of kocumarin, a novel antibiotic isolated from actinobacterium Kocuria marina CMG S2 associated with the brown seaweed Pelvetia canaliculata

Abstract: Kocumarin represents a new promising natural antibiotic for in vivo and environmental applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 54 publications
0
26
0
1
Order By: Relevance
“…Hence, cyanobacteria have some mechanisms for inhibiting the development of RKNs. For example, many forms of cyanobacteria are informed to create a large number of toxic compounds like, nodularins, microcystins, neurotoxins (Holajjer et al, 2013;Gaget et al, 2017) and benzoic acid which produced by microalgae (Uzaira et al, 2018). Cyanobacteria can also depress pathogenic agents by distraction of the cytoplasmic membrane and suppression of the protein creation (Swain et al, 2017).…”
Section: Antagonistic Effects Of the Yeast And Cyanobacteria On Nematmentioning
confidence: 99%
“…Hence, cyanobacteria have some mechanisms for inhibiting the development of RKNs. For example, many forms of cyanobacteria are informed to create a large number of toxic compounds like, nodularins, microcystins, neurotoxins (Holajjer et al, 2013;Gaget et al, 2017) and benzoic acid which produced by microalgae (Uzaira et al, 2018). Cyanobacteria can also depress pathogenic agents by distraction of the cytoplasmic membrane and suppression of the protein creation (Swain et al, 2017).…”
Section: Antagonistic Effects Of the Yeast And Cyanobacteria On Nematmentioning
confidence: 99%
“…Macroalgae are known to host diverse species of actinobacteria, both epiphytic and endophytic, but little has been done to assess their biotechnological potential, with the majority of the bioactivity screenings targeting epiphytic microorganisms, mainly fungi (Egan et al, 2008). Nevertheless, some studies demonstrated that actinobacteria isolated from macroalgae are capable of producing bioactive compounds, including antibiotics, antitumor, and anti-inflammatory compounds (Braña et al, 2015; Uzair et al, 2018). The brown alga Laminaria ochroleuca forms complex structures, known as kelp forests, which dominate shallow rocky shores of cold-water marine habitats worldwide (Franco et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This prevalence may be explained by their spore-forming ability, UV radiation tolerance and other environmental adaptations that ensure survival in harsh conditions. Actinobacterial genera are known for their great potential to produce several bioactive substances 47 , 49 , 50 , although they also have the ability to degrade and use complex organic compounds and for their bioremediation of contaminated soils 51 . In fact, the predictive functional analysis using the Actinobacteria-derived 16S rRNA gene sequences showed enrichment of some functional categories related to carbohydrate metabolism, xenobiotic biodegradation and bioactive compound biosynthesis when compared with the total bacterial community.…”
Section: Discussionmentioning
confidence: 99%